2007
DOI: 10.1016/j.jnoncrysol.2006.09.043
|View full text |Cite
|
Sign up to set email alerts
|

Stability of E′ centers induced by 4.7eV laser radiation in SiO2

Abstract: The kinetics of E' centers (≡Si•) induced by 4.7eV pulsed laser irradiation in dry fused silica was investigated by in situ optical absorption spectroscopy. The stability of the defects, conditioned by reaction with mobile hydrogen of radiolytic origin, is discussed and compared to results of similar experiments performed on wet fused silica. A portion of E' and hydrogen are most likely generated by laser-induced breaking of Si-H precursors, while an additional fraction of the paramagnetic centers arise from a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…This is in accordance with the temperature dependent decay of E 0 -centers reported by Messina and Cannas. 49 Whereas at 200 K the concentration of E 0 -centers remains constant in time, at 300 K these defects are subject to decay. In contrast, NBOHCs are stable after an initial decay due to hydrogen recombination.…”
Section: E Thermal Stabilitymentioning
confidence: 99%
“…This is in accordance with the temperature dependent decay of E 0 -centers reported by Messina and Cannas. 49 Whereas at 200 K the concentration of E 0 -centers remains constant in time, at 300 K these defects are subject to decay. In contrast, NBOHCs are stable after an initial decay due to hydrogen recombination.…”
Section: E Thermal Stabilitymentioning
confidence: 99%
“…The decay of radiation-induced E 0 center in wet and dry silica glass was investigated and it was suggested that the reaction (1) is the mechanism of the decay of E 0 center [5,6]. In this paper attention is focused on the reaction shown in Eq.…”
Section: Discussionmentioning
confidence: 99%
“…It is also known that pre-treatment of silica glasses with hydrogen before irradiation reduces the optical property degradation caused by defect creation by irradiation [3,4]. It was also suggested [5,6] that post UV irradiation annealing of E 0 center was effected by hydrogen produced during the UV irradiation. In this paper, the effect of hydrogen treatment at high temperature on the concentration of E 0 centers in silica glass is reported.…”
Section: Introductionmentioning
confidence: 99%
“…An important feature of the E 0 center, shared by other paramagnetic defects, is that it can be annealed by reaction with diffusing H 2 [10,12,[14][15][16][17][18][19][20]. This process is widely exploited in optical fibers technology where H 2 loading of the SiO 2 core material is used to prevent it from being damaged by UV light.…”
Section: Introductionmentioning
confidence: 99%
“…Since passivation of E 0 by H 2 is thermally activated as well, the presence of hydrogen may be expected to influence the temperature dependence of the formation efficiency of the defects, due to the interplay between generation and passivation. To thoroughly investigate this issue it is needed to measure in situ the kinetics of the defects in temperature-controlled experiments [16,[18][19][20], in contrast with previous works that measured only the stationary concentration of E 0 centers [4,5,[8][9][10][11] …”
Section: Introductionmentioning
confidence: 99%